Psychosocial Factors and Their Relationship With Selfmanagement in People With Type 2 Diabetes Mellitus: A Conceptual Framework Based on Socio-Cognitive Theory - Leili Rabiei; Masoud Lotfizadeh; Mohammad Abbasi; Akbar Babaei Heydarabadi; Reza Masoudi (Shahrekord University of Medical Sciences, 2018)
Background and aims: Maintaining the health of diabetic people depends on the self-management of the disease. This study aimed to evaluate the relationship of distress, self-efficacy, perceived social support, and self-care with self-management behaviors in the patients with type 2 diabetes. Methods: The present analytical-descriptive study was conducted on 228 diabetic patients, during 2016-2017. Most of the participants were male (60.6%) and the mean age of them was 51.95±15.04. The participants were selected based on a simple random sampling method after completing the consent form. The required data were collected through questionnaires of distress, self-efficacy, perceived social support, self-care, and self-management. The data were statistically analyzed using SPSS software version 22.0. Results: Out of 228 participants, 77.3% were married and the highest frequency in terms of educational attainment was related to those with a high school diploma. The results indicated that the duration of affliction with diabetes was less than 10-15 years in 88.9% of the participants. Pearson correlation test demonstrated that the total score of self-management had a significant relationship with the total scores of distress, perceived social support, self-efficacy, and self-care (P<0.005). The results of regression analysis also indicated that distress, perceived social support, self-efficacy, and self-care had a predictive power of 0.43% for self-management. Among these variables, the predictive powers of self-efficacy and self-care were statistically significant, and the prediction rate of self-efficacy was more than that of other ones (β =0.17). Conclusion: The study findings showed that the researchers who want to perform interventions based on cognitive-social theory should mainly focus on self-care and self-efficacy.